Heart rate monitoring of the endurance runner during high intensity interval training: Influence of device used on training functions - Ruiz-Alias, S. A.; García-Pinillos, F.; Soto-Hermoso, V. M.; Ruiz-Malagón, E. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
Photoplethysmography (PPG) heart rate devices are greatly affected by the motion artifacts of running. As a result, their application in training load systems and effort control strategies based on heart rate (HR) could be debatable. In 2019, Polar applied some new features on their PPG devices to improve their accuracy. Thus, the purpose of this study was to determine the level of agreement between the new PPG system Polar Precision Prime™ and the chest strap Polar H10 (reference system) in the HR monitoring during an interval running protocol. A group of 37 long distance runners completed an interval running protocol of 10 min composed of five 1-min trials with an active break of 1-min between each trial. An excellent reliability (ICC > 0.9) was obtained for the entire interval running protocol with the lowest values in the first 2 min (ICC = 0.960-0.949), slight differences between intensities (ICC = 0.992-0.986), and a reduction of the observed tendency (ICC > 0.9) when the Edwards quantification model was applied (ICC = 0.877-0.967). The Bland-Altman plots with the final HR values of each trial establish a systematic bias (<1 bpm) for all intervals with a random error (<4 bpm), except in the first trial which had a higher random error (6.85 bpm). In conclusion, the innovations applied in the new PPG system provide the accuracy required for use in diverse functions, including endurance running.